Benefits and limitations of clinical assessment of abnormal vaginal discharge etiology - T.M. Tutchenko; T.F. Tatarchuk; L.О. Borysova; E.F. Chaikivska (Publishing House TRILIST, 2023)
Abnormal vaginal discharge (AVD) is a common syndrome. Its management is addressed in many evidence-based guidelines: International Union of Sexually Transmitted Infections (IUSTI) and WHO Guidelines for management of vaginal discharge (2018); American College of Obstetrics and Gynecology (ACOG) Practice Bulletin No. 215 «Vaginitis in non-pregnant patients» (2020); U.S. Centers for Disease Control and Prevention (CDC) Guidelines for the treatment of sexually transmitted diseases (2021) etc. In December 2022, the Ministry of Health of Ukraine approved an adapted Clinical Guidelines and Standards of Medical Care "Abnormal vaginal discharge". A special aspect of AVD management is frequent recurrence. Among the many hypotheses of the etiology of the recurrent course of vaginal infections the clinical aspect of difficulties of identifying all pathogens in case of mixed forms deserves special attention. Thus, there is need to presume the possibility of a mixed etiology of AVD or an atypical course of mono-infection at the stage of clinical examination. This review focuses on the role of vaginal discharge pH measuring both in the clinical stage of diagnosing the causes of AVD and in the interpreting laboratory results. Vaginal pH testing is an important component of the clinical stage in diagnostics of the AVD causes. This feasible and quick study allows objectifying the vaginal dysbiosis with a decrease in lactoflora and lactic acid value, which requires further laboratory diagnostics during the examination. Also it is an integral part of the Amsel criteria in the diagnostics of bacterial vaginosis, and vaginal health index to assess the degree of vaginal atrophy in menopause. Vaginal pH testing improves the diagnosis of difficult-to-detect infections and rare causes of AVD. Also, this method is useful for telemedicine to prevent unnecessary medical examinations, laboratory tests and self-treatment, or vice versa, to confirm the need for a specialist consultation.